Extent and Predictors of Decision Regret among Informal Caregivers Making Decisions for a Loved One: A Systematic Review. (November 2020) - Elidor, Hélène; Adekpedjou, Rhéda; Zomahoun, Hervé Tchala Vignon; Ben Charif, Ali; Agbadjé, Titilayo Tatiana; Rheault, Nathalie; Légaré, France
Background: Informal caregivers often serve as decision makers for dependent or vulnerable individuals facing health care decisions. Decision regret is one of the most prevalent outcomes reported by informal caregivers who have made such decisions. Objective: To examine levels of decision regret and its predictors among informal caregivers who have made health-related decisions for a loved one. Data sources: We performed a systematic search of Embase, MEDLINE, Web of Science, and Google Scholar up to November 2018. Participants were informal caregivers, and the outcome was decision regret as measured using the Decision Regret Scale (DRS). Review methods: Two reviewers independently selected eligible studies, extracted data, and assessed the methodological quality of studies using the Mixed Methods Appraisal Tool. We performed a narrative synthesis and presented predictors of decision regret using a conceptual framework, dividing the predictors into decision antecedents, decision-making process, and decision outcomes. Results: We included 16 of 3003 studies identified. Most studies ( n = 13) reported a mean DRS score ranging from 7.0 to 32.3 out of 100 (median = 14.3). The methodological quality of studies was acceptable. We organized predictors and their estimated effects (β) or odds ratio (OR) with 95% confidence interval (CI) as follows: decision antecedents (e.g., caregivers' desire to avoid the decision, OR 2.07, 95% CI [1.04–4.12], P = 0.04), decision-making process (e.g., caregivers' perception of effective decision making, β = 0.49 [0.05, 0.93], P < 0.01), and decision outcomes (e.g., incontinence, OR = 4.4 [1.1, 18.1], P < 0.001). Conclusions: This review shows that informal caregivers' level of decision regret is generally low but is high for some decisions. We also identified predictors of regret during different stages of the decision-making process. These findings may guide future research on improving caregivers' experiences.